The utopian challenge to global capitalism by Walter van den Broeck in Terug naar Walden - Visagie, Andries (Literator, 2012)
The socialist sympathies that inform the writing of Flemish author Walter van den Broeck align him with a well-established tradition of socially engaged writing in Flanders. In his novel Terug naar Walden (Back to Walden), published in 2009, he revisits the Walden project of the Dutch reformer and writer Frederik van Eeden (1860−1932). Van den Broeck suggests that a reconsideration of the socialist ideals that inspired Van Eeden to establish settlements in the Netherlands and the United States is warranted in the light of the economic crisis triggered by unchecked capitalist practices in 2008. In Terug naar Walden Ruler Marsh, the richest man in the world, unleashes a global financial crisis as a form of retaliation against the capitalist system that ruined his parents. Marsh returns to the Kempen in Flanders where his family originated. In a Heideggerean affirmation of the local as exemplified by the country road, Van den Broeck articulates his vision of the common, that theorists Michael Hardt and Antonio Negri in their Empire trilogy have attempted to salvage from communist thinking, with a utopian notion that a stronger connection with the land and the people within one’s immediate environment may provide a useful premise for the development of viable alternatives to capitalism.